2021
DOI: 10.1101/2021.09.07.21263229
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Quantitative measurement of infectious virus in SARS-CoV-2 Alpha, Delta and Epsilon variants reveals higher infectivity (viral titer:RNA ratio) in clinical samples containing the Delta and Epsilon variants

Abstract: Background Novel SARS-CoV-2 Variants of Concern (VoC) pose a challenge to controlling the COVID-19 pandemic. Previous studies indicate that clinical samples collected from individuals infected with the Delta variant may contain higher levels of RNA than previous variants, but the relationship between viral RNA and infectious virus for individual variants is unknown. Methods We measured infectious viral titer (using a micro-focus forming assay) as well as total and subgenomic viral RNA levels (using RT-PCR) i… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“…These four amino acid substitutions might affect the sensitivity of the four RATs. Alternatively, the reduced sensitivity might be caused by a reduction in the particle/PFU ratio of the delta variant [20] because delta variants harboring L452R, E484Q, and P681R in the S protein efficiently infect cells due to the high affinity of the S protein for ACE2 and their high fusion efficiency [21,22]. This means that test specimens prepared at a certain PFU might contain fewer virus particles of the delta variant than of the S-614D virus.…”
Section: Discussionmentioning
confidence: 99%
“…These four amino acid substitutions might affect the sensitivity of the four RATs. Alternatively, the reduced sensitivity might be caused by a reduction in the particle/PFU ratio of the delta variant [20] because delta variants harboring L452R, E484Q, and P681R in the S protein efficiently infect cells due to the high affinity of the S protein for ACE2 and their high fusion efficiency [21,22]. This means that test specimens prepared at a certain PFU might contain fewer virus particles of the delta variant than of the S-614D virus.…”
Section: Discussionmentioning
confidence: 99%
“…At present, Alpha B.1.1.7 (known as 20I/501Y.V1, VOC 202012/01) (9), Beta B.1.351 (known as 501Y.V2) (10), Gamma P.1 (known as 501Y.V3) (11) and Delta B.1.617.2 (known as 478K.V1) (12) are defined as "variants of concern (VOCs)" by the WHO. Several studies have indicated that the Delta variant has higher transmissibility (13)(14)(15) and immune evasion than the early original virus strain and the other three VOCs. COVID-19 patients infected with Delta have a higher risk of hospitalization, ICU admission, and mortality (16)(17)(18).…”
Section: Introductionmentioning
confidence: 99%
“…This is likely due to the cumbersome nature of the assays used to quantify levels of infectious virus coupled with the requirement to perform these assays in a BSL-3 laboratory. However, a recent study found a significant amount of variability in the relationship between viral titers for infectious virus and viral RNA levels (13).…”
Section: Discussionmentioning
confidence: 98%
“…While some studies have described the amount of viable virus shed by individuals infected with the various SARS-CoV-2 variants (12)(13)(14), more studies are needed to better characterize infectious virus levels in vaccinated and unvaccinated individuals. This is especially important because each study uses different methods and focuses on different populations of individuals from different geographic locations.…”
Section: Introductionmentioning
confidence: 99%